2020
DOI: 10.1177/0969733020968215
|View full text |Cite
|
Sign up to set email alerts
|

Predatory nursing journals: A case study of author prevalence and characteristics

Abstract: Background: Predatory publishing poses a fundamental threat to the development of nursing knowledge. Previous research has suggested that authors of papers published in predatory journals are mainly inexperienced researchers from low- and middle-income countries. Less attention has been paid to contributors from high-income countries. Aim: To describe the prevalence and characteristics of Swedish authors publishing in predatory nursing journals. Design: Quantitative descriptive case study. Participants and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 24 publications
(30 reference statements)
0
16
0
Order By: Relevance
“…Many studies have examined predatory journals across academic disciplines. In nursing, research has documented the extent of predatory nursing journals, questionable peer review done by these journals, lack of adherence to editorial standards, limited qualifications of editors and editorial board members, inaccurate information at the journal websites, and poor quality of content in articles (Edie & Conklin, 2019;Gabrielsson et al, 2020;McCann & Polacsek, 2018;Oermann et al, 2016Oermann et al, , 2018Owens & Nicoll, 2019). When articles published in predatory journals are cited in subsequent publications, the information is disseminated beyond the original article into other literature.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have examined predatory journals across academic disciplines. In nursing, research has documented the extent of predatory nursing journals, questionable peer review done by these journals, lack of adherence to editorial standards, limited qualifications of editors and editorial board members, inaccurate information at the journal websites, and poor quality of content in articles (Edie & Conklin, 2019;Gabrielsson et al, 2020;McCann & Polacsek, 2018;Oermann et al, 2016Oermann et al, , 2018Owens & Nicoll, 2019). When articles published in predatory journals are cited in subsequent publications, the information is disseminated beyond the original article into other literature.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Some scholars may simply be naïve to the characteristics and consequences of predatory publications (Pond et al, 2019), but Mills and Inouye (2021) suggest that some faculty may intentionally publish in these journals to advance their careers, with awareness of their personal challenges in publishing, such as English language proficiency, slow reviews, and time to publication in non-predatory journals. In a study of the prevalence and characteristics of Swedish authors who publish in predatory nursing journals, Gabrielsson et al (2020) concluded that publishing articles in predatory journals legitimizes those journals and, importantly, jeopardizes the trustworthiness of nursing knowledge.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Predatory journals have significantly infiltrated the academic publishing world, and many papers have raised awareness about the perils of publishing in such journals. [1][2][3][4][5][6] Predatory journals and conferences are often perceived as two sides of the same coin; nevertheless, literature on predatory conferences (PC) is noticeably lacking. 7 Academic conferences are essential to researchers and an integral part of scientific communication, as they offer an opportunity for sharing research findings, building networks and obtaining valuable new information.…”
Section: Introductionmentioning
confidence: 99%
“…Predatory journals have significantly infiltrated the academic publishing world, and many papers have raised awareness about the perils of publishing in such journals 1–6. Predatory journals and conferences are often perceived as two sides of the same coin; nevertheless, literature on predatory conferences (PC) is noticeably lacking 7.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the prevalence and characteristics of authors publishing in predatory journals have shown that the authors tend to be inexperienced (Bagues et al, 2019; Xia et al, 2015), however experience alone does not explain the author profile as argued by Mertkan, Aliusta, and Suphi (2021). Authors of publications in predatory journals are in some cases highly experienced (Gabrielsson et al, 2021; Wallace & Perri, 2018). Recent studies have explored further characteristics of authors publishing in predatory journals from specific fields and countries.…”
Section: Introductionmentioning
confidence: 99%